Hubungan Antara Indeks Massa Tubuh dan Tingkat Kebugaran Jasmani dengan Mengukur Vo2 Maks pada Nelayan Penyelam di Kelurahan Kedung Cowek Surabaya - Ratih Kumala Sari; Janto Poernomo Hadi; Lena Wijayaningrum (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Background: Body mass index (BMI) is the technique most often used to measure body fat. Physical fitness is the ability of a person to do physical activity. Decreasing physical fitness and increasing body fat are important factors in developing cardiovascular comorbidity. Physical fitness is influenced by factors such as genetics, age, BMI, physical activity, and others. Increased body fat is inversely proportional to VO2max, thus increasing body mass index which causes increased body mass. Aim: To determine the relationship between body mass index and physical fitness level by measuring VO2 Maks in diver fishermen in Kedung Cowek Village Surabaya Research methods: 49 respondents measured height, weight, and VO2 max. BMI is measured by kg / m2 weight / height. VO2 max was measured by Queen’s College Step Test. The correlation is analyzed using Spearman's Rho. Results: The results showed that as many as 23 fishermen (46.9%) with BMI were included in the normal group, 10 fishermen (20.4%) were mild level obese groups, 15 fishermen (30.6%) heavyweight fat groups and 1 fisherman included Mild level BMI. the results of the analysis found a negative correlation that was not significant between BMI and physical fitness level (r = -0.010; p = 0.944). Conclusion: There is no significant relationship between BMI and physical fitness.